2019
DOI: 10.5535/arm.2019.43.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Fall Risk Assessment of Rural Elderly Population in Korea

Abstract: Objective To investigate the risk factors for fall in the elderly population residing in rural areas of Korea and provide useful data for their prevention. Methods As part of farmers’ health promotion project, a retrospective study was conducted with a total of 350 elderly people recruited from March 2016 to December 2016. These subjects were divided into two groups: 254 non-fallers and 96 fallers. A person who fell to the floor at least once in the past year was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…A large number of studies showed that aging is a risk factor for falls. However, the current study found that aging is not a nonlinear correlation risk factor for falls, similar to some previous reports [ 22 , 23 ]. This study showed that the tendency to fall increases with age before 85 years, and then the risk declines at >85 years of age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A large number of studies showed that aging is a risk factor for falls. However, the current study found that aging is not a nonlinear correlation risk factor for falls, similar to some previous reports [ 22 , 23 ]. This study showed that the tendency to fall increases with age before 85 years, and then the risk declines at >85 years of age.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies focused on urban-dwelling elderly reporting that the frequency of falls increases with age, which is not observed in rural areas. A few studies reported that age is not a risk factor for falls, and younger elderly (60–69 years old) suffered more falls and exhibited statistically significant factors related to falls [ 22 ], while another report deemed this feature more probable in the 70–79-year-old age group [ 23 ]. Tripping was the most common cause of a fall in the community [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…considering the higher prevalence of falls in women. older and among those with chronic diseases (23) . As these are non-modifiable conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Falling incidence and fall-related cost in rural elderly population has been studied but separately from urban populations. [ 11 , 12 ] A study by Park et al [ 13 ] about rural region revealed that female gender and older age are risk factors for fall. In a study using data from 16,393 people over 65 in China, Zhang et al [ 14 ] compared the fall characteristics of rural and urban areas.…”
Section: Introductionmentioning
confidence: 99%